Synthetic fertilizers alter floral biophysical cues and bumblebee foraging behavior. Issue 5 (9th November 2022) - Hunting, Ellard R; England, Sam J; Koh, Kuang; Lawson, Dave A; Brun, Nadja R; Robert, Daniel
Abstract: The use of agrochemicals is increasingly recognized as interfering with pollination services due to its detrimental effects on pollinators. Compared to the relatively well-studied chemical toxicity of agrochemicals, little is known on how they influence various biophysical floral cues that are used by pollinating insects to identify floral rewards. Here, we show that widely used horticultural and agricultural synthetic fertilizers affect bumblebee foraging behavior by altering a complex set of interlinked biophysical properties of the flower. We provide empirical and model-based evidence that synthetic fertilizers recurrently alter the magnitude and dynamics of floral electrical cues, and that similar responses can be observed with the neonicotinoid pesticide imidacloprid. We show that biophysical responses interact in modifying floral electric fields and that such changes reduce bumblebee foraging, reflecting a perturbation in the sensory events experienced by bees during flower visitation. This unveils a previously unappreciated anthropogenic interference elicited by agrochemicals within the electric landscape that is likely relevant for a wide range of chemicals and organisms that rely on naturally occurring electric fields.